Physical safety climate, safety practices and perceived well-being of informal solid waste collectors in the Cape Coast Metropolis - Samuel Maneen; Nkosi Nkosi Botha; Mustapha Amoadu; Edward Wilson Ansah (Discover Social Science and Health)
Abstract Background The work environment for informal solid waste collectors keeps deteriorating, which negatively affects the health, safety and well-being of these workers. The study explored the physical safety climate, safety practices and how these variables impact the health and well-being of these informal solid waste collectors within Cape Coast Municipal of Ghana. Methods This cross-sectional survey sampled 120 informal solid waste collectors in the Cape Coast Metropolis. These participants were selected using purposive and convenient sampling methods, where data collection was done in-person. Data were collected using a 43-item questionnaire comprising demographic characteristics, physical safety climate, safety practices, and physical and psychological well-being items. Frequency counts, percentage analysis, bivariate correlation and multiple regression were used to analyse the data. Results The results revealed that 40.8% of the workers perceived their work as high-risk due to low physical safety climate, and 41.7% exhibited poor safety practices while at work. There was also a strong positive relationship between perceived well-being, physical safety climate, and safety practices among the workers. Moreover, after controlling for the demographic factors, hierarchical multiple regression analysis revealed that physical safety climate (B = 0.844; p < 0.001) was significant in predicting perceived health and well-being of the workers. However, safety practices did not significantly predict workers’ well-being (B = 0.067; p = 0.356). Conclusion Informal sold waste collectors in Cape Coast are exposed to poor physical safety climate, which contributes to their poor safety practices while at work. We suggest that Ghana’s quest to achieve Sustainable Development Goals 3, 6 and 8 will be hard to attain unless every worker’s health and well-being is taken seriously.